2020
DOI: 10.1007/s11605-019-04499-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Surgery (ERAS) Reduces Hospital Costs and Improve Clinical Outcomes in Liver Surgery: a Systematic Review and Meta-Analysis

Abstract: Background Enhanced recovery after surgery (ERAS) protocols are evidence-based, multimodal and patient-centred approach to optimize patient care and experience during their perioperative pathway. It has been shown to be effective in reducing length of hospital stay and improving clinical outcomes. However, evidence on its effective in liver surgery remains weak. The aim of this review is to investigate clinical benefits, cost-effectiveness and compliance to ERAS protocols in liver surgery. Methods A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 43 publications
2
101
1
2
Order By: Relevance
“…The analysis results of other secondary outcome measures showed that patients with ERAS protocol had shorter postoperative hospital stay, and there was no statistical difference in 30-day readmission rate, reoperation rate and mortality compared with standard care, indicating that patients with ERAS had faster postoperative recovery and better. A large number of previous studies have shown that ERAS regimen reduces the incidence of common postoperative complications, accelerates the early recovery of intestinal function, accelerates the early postoperative mobilization of patients and reduces the cost of hospitalization [6,[55][56][57][58]. Obviously, ERAS protocol has many advantages compared with the standard care, and according to our study ERAS protocol has no significant impact on the incidence of postoperative AKI, affirming the safety of ERAS protocol on renal function, which is conducive to the further development of ERAS protocol.…”
Section: Plos Onementioning
confidence: 99%
“…The analysis results of other secondary outcome measures showed that patients with ERAS protocol had shorter postoperative hospital stay, and there was no statistical difference in 30-day readmission rate, reoperation rate and mortality compared with standard care, indicating that patients with ERAS had faster postoperative recovery and better. A large number of previous studies have shown that ERAS regimen reduces the incidence of common postoperative complications, accelerates the early recovery of intestinal function, accelerates the early postoperative mobilization of patients and reduces the cost of hospitalization [6,[55][56][57][58]. Obviously, ERAS protocol has many advantages compared with the standard care, and according to our study ERAS protocol has no significant impact on the incidence of postoperative AKI, affirming the safety of ERAS protocol on renal function, which is conducive to the further development of ERAS protocol.…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, hospitalization time of patients has been demonstrated significantly decreased in patients who underwent the modified hysteroscopic-laparoscopic surgery compared with the patients with traditional surgery (4.50±0.50 days vs 5.50±0.75 days) in our study, which is considered to be another parameter for patient's cost. 18,19 Therefore, the modified hysteroscopic-laparoscopic surgery may reduce cost and bring more benefits for patients. Intraoperative bleeding volume is a crucial parameter to evaluate the quality of surgery, and it is significantly related to the recovery of patients after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rapid and large-scale implementation of ERAS program is feasible and effective [11]. Patient-center approach to optimize patients care and experience during the perioperative period, which has been shown to be effective in improving outcomes [12,13].…”
Section: Discussionmentioning
confidence: 99%